Bacteriology of Diarrhea in Peru. Review of work performed - Colichón Arbulú, Héctor (1964)
By the fourth decade of this century the microbial etiology of diarrhea in our country was attributed to protozoa , being dysenterica Ameba the most frequently used to be found by laboratory staff physicians of the past, and the prevailing medical consensus , for reasons obvious , the considered the main agent producing diarrhea s of children and adults who so often had to deal with in the populations of the various regions of Peru . This is a national problem that statistical notes from the first by its incidence , frequency and distribution , the young child who , in the past decades , and terrifying gave higher mortality rates remain . At present, the problem still persists , knowing it is not the dysenterica Shigella and Salmonella Ameba but the main agents that produce them and the child who has the most severe infectious processes , as well as higher mortality rates from these causes .